Wave propagation characteristics of polymeric underground cables - Kuan T.M. (2023)
Knowledge on wave propagation characteristics of both ideal and degraded XLPE cables due to water treeing are the important basics to examine the healthiness of a cable through localization of faults due to water treeing in cables using time domain reflectometry (TDR) measurement technique. In this study, both ideal and degraded XLPE cables are modelled and simulated using MATLAB. The same program is also used to simulate four other cables in different geometries to investigate whether cable geometry influences the results. All results are compiled and compared to determine the wave propagation characteristics of water treeing in XLPE cables. 2011 IEEE.